A stage set for villains - Spann, Shannon J. (Mayhem Books, 2026)
"The gods are dead. All that's left are the Players... The performers of the Playhouse are as worshipped as they are feared, their enchanting shows bending hearts, minds, and even reality itself. Vicious, godlike, lethal. Eighteen-year-old Riven Hesper knows the dangers better than anyone, after her own encounter with a Player resulted in a curse that is slowly killing her. When the Playhouse announces the spectacle of a lifetime--a chance for one mortal to steal a Player's immortality--Riven sees her last chance to live. Desperate for answers, she infiltrates the competition. There, she finds Jude, the Playhouse's brilliant, merciless Lead Player, whose charm is as dangerous as his Craft, and strikes a deadly bargain to save her life. But with time running out and the Playhouse's secrets unraveling into a disturbing picture, Riven faces a grim possibility: she might not be the hero of her story after all. In fact, she may be the villain. Because the Playhouse doesn't just tell stories. It rewrites them. And Riven's might end in blood" --Front sleeve.